THE UNEXPECTED BENEFITS OF MIXED-LEVEL CLASSROOMS IN UZBEKISTAN - Roza Utaganova Mamadiyor qizi (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
The heterogeneous language classroom, often viewed as a challenge for educators, holds significant potential for enriching the educational experience. In the context of Uzbekistan's evolving educational landscape, this article argues that a mixed-ability classroom is not a hurdle to be overcome, but a valuable asset to be leveraged. By shifting the perspective from a deficit model to a resource-oriented one, teachers can foster a more dynamic, collaborative, and authentic learning environment that benefits students at all proficiency levels and aligns with cultural values of community and mutual support.